Optical Metrology with many faces - Kujawińska, Małgorzata (Photonics Letters of Poland, 2012)
A brief editorial overview of the current issue is presented. This special issue of Photonics Letters of Poland devoted to optical metrology contains 15 invited and regularly submitted letters showing a wide range of optical measurement and characterization methods, data processing procedures and their applications.